The Gene : A historical perspective - Ted Everson (Greenwood guides to great ideas in science.)
A history of the science of genetics discusses its roots in heredity, the discovery of DNA, the Human Genome Project, the applications of genetic work, and the controversy surrounding genetic engineering.